Bandgap engineering and modulation of thermodynamic, and optical properties of III-N monolayers XN (X = In, Ga & Al) by mutual alloying. (1st September 2022) - Kumar, Nilesh; Chaurasiya, Rajneesh; Karlicky, Frantisek; Dixit, Ambesh
Abstract: We investigated the structural, thermodynamic, and optoelectronic properties of Inx Al1−x N, Inx Ga1−x N, and Gax Al1−x N alloys for x = 0.25, 0.50 and 0.75. The optimized lattice constants showed nearly a small deviation trend from Vegard's law with composition x. The impact of mutual alloying is evaluated in terms of enthalpy and interaction parameters. The calculated electronic band structures and density of states lie in the bandgap ranges from 1.09 eV to 2.72 eV for composition x 0.25 to 0.75. These electronic properties suggested that alloys are suitable bandgap semiconductors with large variations in their bandgap energies for optoelectronic applications. The optical properties are calculated using the dielectric constant and correlated with the calculated electronic band structures. The main reflectivity peak and absorption coefficient showed a significant shift with increasing x. These monolayers' suitable bandgap and optoelectronic properties make them attractive for optoelectronic applications, including photovoltaics and photodetectors.